TRPM2: bridging calcium and ROS signaling pathways—implications for human diseases - Maliougina, Maria; El Hiani, Yassine (Frontiers in Physiology, 2023)
• TRPM2 converts ROS signal into a Ca 2+ signal.• TRPM2 is involved is various disease.• Both activation and inhibition of TRPM2 could be used in therapy. ABSTRACT TRPM2 is a versatile and essential signaling molecule that plays diverse roles in Ca 2+ homeostasis and oxidative stress signaling, with implications in various diseases. Research evidence has shown that TRPM2 is a promising therapeutic target. However, the decision of whether to activate or inhibit TRPM2 function depends on the context and specific disease. A deeper understanding of the molecular mechanisms governing TRPM2 activation and regulation could pave the way for the development of innovative therapeutics targeting TRPM2 to treat a broad range of diseases. In this review, we examine the structural and biophysical details of TRPM2, its involvement in neurological and cardiovascular diseases, and its role in inflammation and immune system function. In addition, we provide a comprehensive overview of the current knowledge of TRPM2 signaling pathways in cancer, including its functions in bioenergetics, oxidant defense, autophagy, and response to anticancer drugs.